Maternal Bradycardia Associated with Betamethasone Administration During Pregnancy - Mojirayo A. Sarumi; James W. Hole; Robert B. Gherman (Case Reports in Obstetrics and Gynecology)
Background. Maternal risks of betamethasone have been rarely reported. Case. At 36 weeks’ gestation, a previously healthy 23-year-old gravida with fetal intrauterine growth restriction was admitted to the hospital for steroid administration. Twenty-six hours after the first dose of betamethasone, a maternal bradycardia was initially noted and eventually nadired at 41 beats per minute. Consultation with the cardio-electrophysiology service revealed no other apparent etiologies for the sinus bradycardia. Due to the asymptomatic nature of the maternal bradycardia, pharmacologic interventions were not recommended. With observation alone, a normal maternal heart rate returned by forty-nine hours after the original betamethasone injection. The patient subsequently had an uneventful intrapartum course. Conclusion. Maternal bradycardia can be associated with antenatal betamethasone administration. Due to the transient nature of this side effect, expectant management is recommended as the treatment option for asymptomatic patients.